Earnings Management: Boon or Bane for Growth in Indonesia Consumer Sector? English - Hamdani, Ujang Halim; Priyanto, Panji; Suhandi, Ni Putu Mila (Training & Research Institute - Jeramba Ilmu Sukses (TRI-JIS), 2024)
This study investigates the relationship between earnings management and financial risk on company growth in the Primary Consumer Goods Industry sector listed on the IDX from 2017 to 2021. The findings show that earnings management practices positively and significantly impact company growth, indicating that companies implementing management profits tend to experience higher growth (Growth Companies). Enhancing positive and efficient earnings management practices can improve company performance and overall business growth. The statistically significant effect indicates that this relationship is not coincidental, emphasizing the strong relationship between earnings management and firm growth. However, financial risk does not significantly affect company growth and cannot moderate the relationship between earnings management and company growth. This observation highlights the complexity of the impact of financial risk on corporate growth, which various unmeasured factors, including changes in interest rates, market fluctuations, and credit risk, may influence. Other internal and external factors that affect the relationship between financial risk and firm growth may not be considered in this regression model, limiting its ability to capture the subtleties of this relationship fully. Nonetheless, this study shows that Financial Risk and Earnings Management significantly affect the dependent variable, Company Growth. The results show that companies that apply better earnings management practices in their financial reporting experience better or higher growth. However, this study had limitations, and future research should explore a different sector, as this may yield different results. In addition, future research may consider including control variables such as firm size, liquidity, leverage, industry growth, and other economic factors to understand their impact on firm growth better